An equivalent mechanism model for kinematic accuracy analysis of harmonic drive. (July 2022) - Dong, Huimin; Dong, Bo; Zhang, Chu; Wang, Delun
Abstract: The kinematic accuracy analysis of harmonic drive (HD) is very complex since there is a compliant cup. To explicitly figure out the effects of errors on the kinematic accuracy of HD, an equivalent mechanism in kinematics of HD is proposed, in which a spatial gear-linkage with 3-R, 2-S pin, 1-P and 1-Gear pair is equivalent to the HD with single pair of teeth of flexspline and circular spline. The kinematic model/equations of the mechanism under error condition are established by means of the mechanism topological structure analysis. For multiple tooth pairs' engagement in HD with load, a similar parallel mechanism with multi-branch of the single tooth pair is then established and a compatibility equation is derived from the identical output motion caused by all branches. With the mechanism model, the kinematic accuracy/transmission error (TE) of HD can be investigated with consideration of errors and deformation caused by load. The TE effects of assembly errors and geometry errors are simulated. The FE analysis and test of a HD are conducted to validate the proposed mechanism model. The FE and test results show good agreement with the simulations', which indicates that the proposed mechanism model is reasonable and effective.